PENDIDIKAN KERAKTER BERBASIS KEARIFAN LOKAL MELALUI MEDIA POSTER TIGA BAHASA PADA SD RAMA SEJAHTERA KOTA MAKASSAR - Abd. Hakim Naba; Endang Ruswiyani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract: Character Education Based on Local Wisdom through Three Language Poster Media at SD Rama Sejahtera Makassar City. This research aimed to find out the implementation of character education activities based on local wisdom through poster media in schools with three languages ​​to stimulate children, to know the role of poster media in character education based on local wisdom, and to know the impact of moral messages conveyed through poster media. This type of research used qualitative descriptive approach. This research was in SD Rama Sejahtera. The technique of determining the informants in this research was proportional sampling. Data collection through field research was carried out by triangulation method, namely: interview, questionnaire, and documentation. This success was a form of good cooperation from every citizen in the school and parents of students in creating the conditions of school culture and the consistent application of character values ​​based on local wisdom through the three language poster media. The implementation of character education based on local wisdom through the three language poster media was realized through the inculcation of character values ​​in the layers of school culture, namely through the provision of adequate facilities and infrastructures to support various activities in school programs as well as being familiarized in daily life at school.